Design of NB-IoT Based Household Light Electric Energy Monitoring System - Pasaribu, Stevan Togar; Asvial, Muhamad (International Journal of Electrical, Computer, and Biomedical Engineering, 2024)
Energy is a vital part of human life, especially in the digital era that requires a lot of energy. Monitoring energy use, especially electricity, is an alternative step to improve energy efficiency. This research aims to develop and implement an NB-IoT-based electrical energy monitoring. The proposed system allows users to monitor, analyze their electrical energy consumption efficiently. Then the Quality-of-Service test results at 500 m get very good results, with the results: average RSSI of -62.8 dBm, average latency of 3.0667 seconds, and PDR ratio of 100%. Quality of Service testing at 1 km gets pretty good results, with the results: average RSSI of -68.933 dBm, average-latency 3.24138 seconds, and PDR ratio of 90%. Quality of Service testing at 1.5 km gets fewer good results, especially on RSSI and PDR parameters, with the results: average RSSI of -84.80 dBm, average-latency 3.4667 seconds, and PDR ratio of 83.33%. The NB-IoT network is suitable for on-grid electricity meters in urban areas with an optimal distance of 500 to 1 km, while at more than 1.5 km it is better used for household scale.